MERANG MUSHROOM CULTIVATION GAMPONG LAMSITEH COT KUTA MALAKA SUB-DISTRICT ACEH BESAR DISTRICT: BUDIDAYA JAMUR MERANG GAMPONG LAMSITEH COT KECAMATAN KUTA MALAKA KABUPATEN ACEH BESAR - Novi Mailidarni; Sulaiman; Juliawati; Tasliati Djafar; Syarifuddin (PT. ROCE WISDOM ACEH, 2025)
This community service program was conducted in Lam U Village, Ingin Jaya District, Aceh Besar Regency, to empower local farmers through the cultivation of oyster mushrooms (Pleurotus ostreatus). The program focused on introducing oyster mushroom cultivation as an alternative agricultural activity to support the local economy. Training on the proper techniques for cultivation, including the preparation of substrates, inoculation, and maintenance of optimal growth conditions, was provided to the participants. The program also emphasized the benefits of oyster mushroom cultivation as a sustainable and profitable agricultural practice. The training sessions were interactive, with hands-on demonstrations to ensure effective knowledge transfer. As a result, participants gained valuable skills that can be applied in their farming practices, contributing to enhanced local economic development.